The Potential of Breadfruit Seed and Jackfruit Seed as Alternative Replacement Medium of Potato Dextrose Agar (PDA) with Seedling F0 Mushrooms - Suparti, Suparti; Agustina, Lina; Agustina, Putri; Rahmawati, Resti (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
Potato Dextrose Agar (PDA) is the most media to grow the mushrooms, but the price of this media is expensive. Thus we need alternative media that easy and cheap to get it. This study aims to determine the growth of Aspergillus niger in alternative Artocarpus communis and Artocarpus heterophyllus seeds media. This research was an experimental study using a completely randomized design (CRD) one factor was the type of media is PDA (M0), Artocarpus communis seed media (M1), Artocarpus heterophyllus seed media (M2) and using the test mushrooms A. niger (J1). Inoculation of A. niger used agar block method for 3 days with a temperature of 28°C. Parameter of research was colony diameter and sporulation of A. niger. Data obtained with qualitative and quantitative methods. The result of this research showed that the best growth for Aspergillus niger was after 72 hours incubation. Colony diameter continually in PDA media, Artocarpus communis media, and Artocarpus heterophyllus media is 4.7 cm, 4.3 cm, and 4.1 cm with heavy sporulation. Therefore, Artocarpus communis and Artocarpus heterophyllus seeds media can be utilized as a substitution of PDA media for the growth of mushrooms.